2009
DOI: 10.2152/jmi.56.6
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative stress of hyperglycemia and the inflammatory process in endothelial cells

Abstract: Hyperglycemia and insulin resistance are common in many critically ill patients. Hyperglycemia increases the production of reactive oxygen species in cells, stimulates the production of the potent proinflammatory cytokines IL-8 and TNF-alpha, and enhances the expression of haem oxygenase-1, an inducible stress protein. It has been shown that administration of insulin and the semi-essential amino acid glutamine have been beneficial to the septic patient. The aim of our study is to test whether these two molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Furthermore, High glucose stress was used to induce insulin resistance in HUVEC cells [23]. High glucose concentration directly contributes to endothelial dysfunction [24], amplified monocyte adhesion and upregulated P-selectin expression [25]. We found that expression of miR-492 was reduced significantly, whereas the resistin was increased at mRNA and protein levels, similar to the results in aortas endothelial tissues from apoE-null mice.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, High glucose stress was used to induce insulin resistance in HUVEC cells [23]. High glucose concentration directly contributes to endothelial dysfunction [24], amplified monocyte adhesion and upregulated P-selectin expression [25]. We found that expression of miR-492 was reduced significantly, whereas the resistin was increased at mRNA and protein levels, similar to the results in aortas endothelial tissues from apoE-null mice.…”
Section: Discussionsupporting
confidence: 76%
“…The increased oxidative damage may be a consequence of hyperglycemia and hyperlipidemia as discussed elsewhere [4, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia increases the production of reactive oxygen species in cells and stimulates the release of the potent proinflammatory cytokines such as IL-8 and TNF-alpha. 2 Several recent studies have shown that impaired fasting glucose (IFG) in diabetes is a risk factor for arterial stiffness [3][4][5][6][7][8] and CVD, 9 but the impact of a slightly high-normal glucose level remains controversial and there are few studies to investigate the relationship between high-normal FPG and increased arterial stiffness. 8 The precise mechanisms by which the level causes CVD and mortality remain unelucidated.…”
Section: Introductionmentioning
confidence: 99%